IMPLEMENTASI PASAL 1365 KUH PERDATA ATAS HAK AHLI WARIS SEBIDANG TANAH BERDASARKAN SURAT TANAH TRADISIONAL DI DESA JATILUWIH - Agus David Trsitan Ananta; Kusuma, putu riski ananda; setianto, muhamad jodi; Dantes, Komang Febrinayanti (Jurnal Ilmu Hukum Sui Generis, 2025)
those who are proven guilty based on Article 1365 of the Civil Code are obliged to compensate for these losses. The problem is how someone is liable for losses resulting from PMH that has been carried out, regarding a plot of land owned by the sole heir who has the marital status of Sentana Rajeg Putrika, based on the old right to the land in the form of a Petok D Land Certificate in the name of his late mother. This research aims to find out (1) the implementation of Article 1365 of the Civil Code in Jatiluwih Village (2) What are the efforts and obstacles of heirs in obtaining rights to their land. The location of this research was carried out in Jatiluwih Village using an empirical legal research system. The technique used in this research is a non-probability technique and the method used to determine research subjects is the Purposive Sampling technique. The results of the research show that the implementation of Article 1365 of the Civil Code in Jatiluwih Village has never been used to resolve cases classified as Unlawful Acts (PMH) because the majority of people in Jatiluwih Village and also Jatiluwih Village Officials do not know or understand the existence of this article. , so that all case resolution in Jatiluwih Village is limited to the mediation level carried out at the Jatiluwih Village Office which is closed with a Letter of Agreement between the two parties in conflict. Regarding the efforts made by the heirs in obtaining rights to their land, it actually needs to be appreciated because the heirs concerned have tried to carry out the objectives of the creation of Law of the Republic of Indonesia Number 5 of 1960 concerning Basic Agrarian Principles Regulations regarding the conversion of old rights to become Freehold Title. It's just that in this research, the heir experienced an obstacle caused by the head of the hamlet concerned who had a basic misunderstanding of the law by not trusting authentic evidence which showed that the heir was the sole heir to the plot of land which was carefully researched and committed acts of abuse of power.